Continuous Performance Engineering In Devops: Integrating Load Testing Into Ci/Cd Pipelines - Gaurav Rathor (Journal of Informatics Education and Research, 2025)
Because release cycles are getting shorter and systems are getting more complicated, Continuous Performance Engineering (CPE) is now a must in DevOps setups. Conventional performance testing methodologies, frequently conducted late in the development lifecycle, are insufficient for early detection of performance regressions. This hypothetical study investigates the incorporation of automated load testing into Continuous Integration and Continuous Deployment (CI/CD) pipelines to facilitate proactive performance validation. The research utilizes an experimental methodology to assess application performance, fault detection rates, and deployment dependability before and after embedding load testing within CI/CD workflows. When continuous load testing is used, percentage-based results show that performance stability improves, performance bottlenecks are found early, and first-time deployment success rates are greater. The results show that Continuous Performance Engineering leads to faster feedback loops, better use of resources, and more dependable software delivery. This means that performance assurance is in line with DevOps ideals of automation, agility, and continuous improvement.